2019
DOI: 10.1007/s12105-019-01003-7
|View full text |Cite
|
Sign up to set email alerts
|

HPV-Related Papillary Lesions of the Oral Mucosa: A Review

Abstract: Human papillomaviruses (HPVs) are causative of a group of clinically papillary lesions. The HPV-related lesions of the oral cavity include squamous papilloma, condyloma acuminatum, verruca vulgaris, and multifocal epithelial hyperplasia. Benign entities, such as verruciform xanthoma or giant cell fibroma, as well as malignancies, such as papillary squamous cell carcinoma and verrucous carcinoma, may be considered in the clinical and/or histologic differential diagnoses of these lesions. Mechanisms of infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
86
0
22

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(110 citation statements)
references
References 54 publications
(193 reference statements)
2
86
0
22
Order By: Relevance
“…Over the last decade, it has been shown that HPV infection represents a cause for a subset of oral squamous cell carcinoma (OSCC). 1,4 A recent study found an increased incidence (ranging from approximately 50% to 225%) of HPV-associated OSCCs. HPV-16 is the most prevalent type, being present in at least 90% of HPV-associated OSCCs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the last decade, it has been shown that HPV infection represents a cause for a subset of oral squamous cell carcinoma (OSCC). 1,4 A recent study found an increased incidence (ranging from approximately 50% to 225%) of HPV-associated OSCCs. HPV-16 is the most prevalent type, being present in at least 90% of HPV-associated OSCCs.…”
Section: Discussionmentioning
confidence: 99%
“…3 HPV 11,16, and 18 are strongly associated with malignant transformation, especially in the oropharynx. 4 HPV 11,16, and 18 are found within the neoplastic cells. Of note, the hypothesis of their oncogenic potential is supported by several observations: the virus's epithelial tropism, the wellknown etiologic role of HPV in almost all squamous cell carcinomas (SCC) of the uterine cervix and in approximately 40% of the cases of other SCCs, and the histological similarities between the epithelium of the uterine and oral mucous membranes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually pedunculated, colors range from white to pink/red and generally presenting as a solitary lesion, which are different from those in this case. 1 Condyloma accuminatum—Correct. Condyloma accuminatum in the oral cavity is a rare disease, it is sexually transmitted, and is most common in adults.…”
mentioning
confidence: 99%
“…Koilocytes may be observed in the upper spinous layer, and there is a chronic subepithelial inflammatory infiltrate and dilated capillaries in the lamina propria. 1 , 2 Heck disease—Incorrect. Rare and benign disease.…”
mentioning
confidence: 99%